Politeness Strategy and Social Power in Animal Farm - Widia Puspa Negara; Intan Mutia; Noval Miftahul Ihsan; Nadya Nurjanah; Devita Ibnu Wardani (Indonesian Journal of Innovation Multidisipliner Research, 2026)
Politeness strategies as a reflection of social power: A study of Animal Farm by George Orwell a pivotal difference with regard to prior studies is that this paper does not concern itself primarily with ideological and political questions but rather examines the function of linguistic politeness as a medium for asserting power. This research used a descriptive qualitative method to analyze data from the dialogues, utterances, and commands of characters through Brown and Levinson’s theory of politeness as well as Bourdieu’s concepts of symbolic power. The results found four politeness strategies which are bald-on-record, positive politeness, negative politeness and off record strategy. The analysis also illustrates how language is both a means of and an end to conserving symbolic, political, informational, and institutional authority. Communicative practices also evolve with changing relations of power across the narrative. They begin as a source of solidarity and trust, before becoming tools for manipulation and rationalising inequalities. As authority becomes total, indirect statements are incrementally replaced by explicit and blunt expressions. Hence, in Animal Farm polite language plays a role not only to work on the interpersonal or the social level but also as rhetoric for persuasion and manipulation of power over others by certain characters within an unequally organized society.